Assessing Physical Performance in Centenarians: Norms and an Extended Scale from the Georgia Centenarian Study. (23rd August 2010) - Cress, M. Elaine; Gondo, Yasuyuki; Davey, Adam; Anderson, Shayne; Kim, Seock-Ho; Poon, Leonard W.
Abstract : Centenarians display a broad variation in physical abilities, from independence to bed-bound immobility. This range of abilities makes it difficult to evaluate functioning using a single instrument. Using data from a population-based sample of 244 centenarians (M Age = 100.57 years, 84.8% women, 62.7% institutionalized, and 21.3% African American) and 80 octogenarians (M Age = 84.32 years, 66.3% women, 16.3% institutionalized, and 17.5% African American) we (1) provide norms on the Short Physical Performance Battery and (2) extend the range of this scale using performance on additional tasks and item response theory (IRT) models, reporting information on concurrent and predictive validity of this approach. Using the original SPPB scoring criteria, 73.0% of centenarian men and 86.0% of centenarian women are identified as severely impaired by the scale's original classification scheme. Results suggest that conventional norms for older adults need substantial revision for centenarian populations and that item response theory methods can be helpful to address floor and ceiling effects found with any single measure.